Civic Literacy in the information age: a survey of vocational high school student in Sidoarjo, Indonesia - Ken Ayu Yalu Puspaningtyas; Fitri Mutia; Asmadi Mohammed Ghazali (Cogent Social Sciences)
Civic literacy is an essential ability that every citizen needs to have in the information age. Lack of civic knowledge and skills can result in actions such as easily provoked behavior or disinformation from fake political information spread online (hoax). This study aims to describe the civic literacy condition of public vocational high school (SMKN) students in Indonesia. The study uses a quantitative approach to measure the phenomenon of civic literacy in vocational school. Online questionnaires were distributed to 200 respondents from five public vocational schools in Sidoarjo, Indonesia, including SMKN 1 Buduran, SMKN 2 Buduran, SMKN 3 Buduran, SMKN 1 Sidoarjo, SMKN 1 Jabon. Three components are used to describe the student’s civic competency: knowledge, skills, and attitudes & values. The results of this study show that the civic competence of vocational high school students is high, with detailed knowledge competency at 4.09, skills at 4.00, and attitude & value at 4.21. This assessment indicates that vocational school students are tolerant with society and the environment, either in their lives or at school. A recommendation for vocational schools in Sidoarjo, schools can provide a space for students to express their aspirations, whether related to phenomena in the field or those within the school. The space or platform that the school can offer may include a digital magazine or a webpage serving as a space for students to explore knowledge, skills, and attitudes in expressing their aspirations. This way, students can fill the page with content (articles or videos) that align with their talents and interests.